Distribution and phylodynamics of papaya ringspot virus on Carica papaya in Cuba - Cabrera Mederos, Dariel (2018)
Orchard and garden papaya crops grown in 47 Cuban municipalities were surveyed from 2008 to 2013, revealing the widespread distribution of papaya ringspot virus (PRSV) in Cuba. Phylodynamic analyses performed with the partial coat protein gene of all Cuban PRSV‐P isolates (34 sequences) and 107 sequences of isolates from the American continent and the Caribbean islands showed a most recent common ancestor in 1942 (95% highest posterior density, HPD 95% = 1911–1967). The substitution rate was estimated to be 7.7 × 10−4 substitutions per site per year (HPD 95% = 4.6 × 10−4 to 1.1 × 10−3), which is equivalent to those detected in other RNA viruses. Demographic reconstruction of PRSV showed that viral diversity increased in the 1985–1990 period, which coincides with the implementation of extensive production practices. Moreover in Cuba, viral dispersion occurred from Mexico and other unknown ancestral locations. The spatiotemporal diffusion analysis proposed Mexico as an ancestral area for the origin of diversification in the American continent and suggests new dispersion events between American and Caribbean isolates. The observed widespread distribution, clear geographic grouping of Cuban isolates, virus growth and genetic diversity provide strong evidence of the PRSV dispersion patterns, which has implications for the control strategies of PRSV.